FACTORS AFFECTING THE DECISION TO ENGAGE IN PRIVATE BUSINESS OF PRIVATE COMPANIES'EMPLOYEES - Kitkanda, Piriyakan; Vigripat, Tawan; srisatanon, pornpana (Journal of MCU Phetchaburi Review, 2023)
The objectives of this research were 1) to study motivation factors affecting the personal business decisions. 2) To compare private business engagement decisions to the characteristics of private company employees. 3) to study the motivational factors affecting the engagement decisions of private company employees. The sample consisted of 385 private company employees. The instrument used for data collection was a questionnaire. Statistics used in data analysis were mean, standard deviation, t-test, one-way ANOVA, and multiple regression analysis.The results showed that: 1) Motivating factors, in general, had the highest average level. Private company employees' personal business engagement decisions were found to be at the highest average level. 2) Employees of private companies with different genders, ages, education levels, marital status, and average monthly income made a significant difference in their decision to run their own business with a 0.05 level of significance. 3) 3 motivation factors affecting the decision to run their own business: the demanding aspect, value aspect, motivation aspect, all of which 3 variables could explain the variation in self-employment decision-making of employees of private companies at 37.90%.